Pengaruh Perencanaan Karir Terhadap Komitmen Karir dan Kepuasan Karir melalui Pengembangan Karir sebagai Variabel Intervening: The Effect of Career Planning on Career Commitment and Career Satisfaction through Career Development as an Intervening Variable - Febriansah, Rizky Eka (Universitas Muhammadiyah Sidoarjo, 2019)
The idea of empowering human resources to create the best service for customers can be started through employee’s career planning in an organization by using HR practices and policies to develop a variety of mindset, abilities, and competencies with the ultimate goal of acquiring new consumers while maintaining existing customers. This study explores the relationship between career development towards career satisfaction along with career commitment via career development as an intervening variable. The research sample of 37 employees from the Business Service Division of PT Telekomunikasi Indonesia showed that there was a significant relationship amongst career planning along with career satisfaction, career planning along with career commitment, as well as career planning along with career satisfaction through career development.